Female subjectivity and spatial displacement in selected coming-of-age novels by Joyce Carol Oates - Chen, Mi (2024)
The exploration of female subjectivity within the framework of spatial displacement presents significant challenges in literary studies, especially when analyzing the coming-of-age novels of American author Joyce Carol Oates. The research in this field is relatively insufficient, so further academic attention is needed. As one of the most prolific contemporary American writers, Joyce Carol Oates’s work spans over half a century, offering profound insights into identity issues in complex environments. This study conducts a textual analysis of four selected coming-of-age novels by Oates—Foxfire: Confessions of a Girl Gang, I’ll Take You There, The Gravedigger’s Daughter, and Mudwoman—to investigate the challenges faced by female characters in their environments and how they navigate these challenges through spatial interactions. The primary challenges these women face include social oppression, gender inequality, identity crises, and the struggle to find selfdefinition within multiple spaces. Their journeys of growth and self-discovery are often accompanied by spatial displacement and conflicts with societal norms as they contend with external pressures and internal conflicts. These female characters ultimately overcome these challenges through interactions within physical, social, and mental spaces, gradually establishing their subjectivity and identity. The study has three objectives: first, to examine how changes in physical space trigger crises and influence the development of female subjectivity; second, to investigate how interactions within expanded social spaces, particularly heterotopias, affect women’s confrontation with and resistance to societal discipline; and third, to analyze how epiphanies and psychological development within mental spaces contribute to the construction and expression of female subjectivity. This research constructs a theoretical framework by synthesizing spatial theories from Lefebvre, with his triadic conceptualization of space, and Foucault, with his insights into heterotopia and power. This framework informs the analysis of the interconnection between spatial displacement and female subjectivity, highlighting female protagonists’ challenges and how these spatial experiences influence their growth and self-discovery. The significance of this study lies in its comprehensive approach to dissecting the spatial elements within Oates’s coming-of-age novels, a perspective that previous research has often overlooked. The findings reveal that spatial displacement is a critical element in subjectivity construction, influencing the development of female subjectivity and challenging traditional constructions of female identity. The findings of this study not only have far-reaching implications for literary analysis and provide new perspectives for multidisciplinary dialogue on space, gender, and subjectivity. This research method can be widely applied to other academic contexts, offering a more comprehensive understanding of how space influences identity formation and subjectivity development, thus fostering a more diverse and enriched interdisciplinary research.